Rights of suspect and accused under Islamic and Malaysian law - Md. Hashim, Ashraf (International Law Book Services, 2004)
This book analyses the Islamic viewpoint on the rights of a suspect or an accused at all stages of criminal procedures. Al-Qur’an, al-sunnah and other sources of Islamic Law have been the basis of discussion. The opinion of the four established sunni schools have also been referred to. The findings are thereafter compared with Malaysian law. It has been observed that there are more similarities than differences between the two systems of law. In some aspects where there are differences, it is hoped that the implementation of suggestions made throughout this book could harmonise the differences and at the same time refined laws could be introduced in order to maintain justice.